2023
DOI: 10.3390/cryst13010132
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Occlusion of Doxorubicin and Hydrogels in CaCO3 Composites for Controlled Drug Release

Abstract: Extensive exploration is required to deploy mineralization as a tool to develop low-cost yet efficient sustained drug release systems. Unlike previous studies which directly incorporated drug components in mineralized products, we propose an emerging approach to synthesizing drug-loaded CaCO3 composites, relying on the synergistic occlusion of the molecular solutions comprising both the alginate hydrogel matrices and the associated drug (doxorubicin) in the course of mineralization. Independent tools including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…To date, studies have shown that CaCO3 has seven phases, including amorphous calcium carbonate (ACC) [5], calcium carbonate monohydrate (monohydrocalcite) [6], calcium carbonate hexahydrate [7], rhombohedral calcite [8], orthorhombic aragonite [9], and hexagonal vaterite [10], as well as the newly discovered phase calcium carbonate hemihydrate [11]. In addition, CaCO3 or CaCO3-based materials processes significant applications, especially in bone regeneration and drug delivery due to its excellent biocompatibility [12][13]. However, CaCO3 can exist in different morphologies and crystal structures, some of them might serve as scaling to reduce the oil recovery.…”
Section: Introductionmentioning
confidence: 99%
“…To date, studies have shown that CaCO3 has seven phases, including amorphous calcium carbonate (ACC) [5], calcium carbonate monohydrate (monohydrocalcite) [6], calcium carbonate hexahydrate [7], rhombohedral calcite [8], orthorhombic aragonite [9], and hexagonal vaterite [10], as well as the newly discovered phase calcium carbonate hemihydrate [11]. In addition, CaCO3 or CaCO3-based materials processes significant applications, especially in bone regeneration and drug delivery due to its excellent biocompatibility [12][13]. However, CaCO3 can exist in different morphologies and crystal structures, some of them might serve as scaling to reduce the oil recovery.…”
Section: Introductionmentioning
confidence: 99%
“…To date, studies have shown that CaCO 3 has seven phases, including amorphous calcium carbonate (ACC) [5], calcium carbonate monohydrate (monohydrocalcite) [6], calcium carbonate hexahydrate [7], rhombohedral calcite [8], orthorhombic aragonite [9] and hexagonal vaterite [10], as well as the newly discovered phase, calcium carbonate hemihydrate [11]. In addition, CaCO 3 or CaCO 3 -based materials have significant applications, especially in bone regeneration and drug delivery due to their excellent biocompatibility [12,13]. However, CaCO 3 can exist in different morphologies and crystal structures, and some of them might result in scaling, reducing oil recovery in oilfields.…”
Section: Introductionmentioning
confidence: 99%